Automatic capture management may cause unnecessary battery depletion in selective his‐bundle pacing - Hung‐Pin Wu; Jan‐Yow Chen; Kuo‐Hung Lin; Kuan‐Cheng Chang (Clinical Case Reports, 2020)
Abstract A routine change in the automatic capture management algorithm from “adaptive” to “off or monitor” is required to conserve device longevity in a permanent pacemaker with His‐bundle pacing.